2019
DOI: 10.3389/fendo.2019.00198
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-Related Immune Modulation of Pregnancy and Labor

Abstract: Pregnancy involves a complex interplay between maternal neuroendocrine and immunological systems in order to establish and sustain a growing fetus. It is thought that the uterus at pregnancy transitions from quiescent to laboring state in response to interactions between maternal and fetal systems at least partly via altered neuroendocrine signaling. Progesterone (P4) is a vital hormone in maternal reproductive tissues and immune cells during pregnancy. As such, P4 is widely used in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 281 publications
3
128
0
7
Order By: Relevance
“…Both, progesterone and glucocorticoids, are significantly involved in the regulation of immune responses (4,7,11). The structural similarities between glucocorticoids and progesterone raise the intriguing concept of mutual, interrelated as well as individual pathways elicited by these hormones.…”
Section: Progesterone and Glucocorticoid Receptors In Immune Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both, progesterone and glucocorticoids, are significantly involved in the regulation of immune responses (4,7,11). The structural similarities between glucocorticoids and progesterone raise the intriguing concept of mutual, interrelated as well as individual pathways elicited by these hormones.…”
Section: Progesterone and Glucocorticoid Receptors In Immune Cellsmentioning
confidence: 99%
“…The genomic effects of progesterone and glucocorticoids are mediated by the intracellular progesterone and glucocorticoid receptors (PR and GR), which belong to a subfamily of the nuclear receptor superfamily (4,7,12). Upon binding to ligands, PR and GR translocate to the cell nuclei, where they interact with specific regions of the DNA to act as transcription factors that modulate gene expression (7,11,12).…”
Section: Progesterone and Glucocorticoid Receptors In Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, similar to the dose-dependent effects of E2 on the immune system [190], adequate and balanced levels of androgens may contribute to preventing negative health outcomes in women after menopause. Similarly to E2 and androgens, high levels of progesterone may also suppress the activity of RA and MS via the inhibition of Th1 pathways [206,207]. On a neural level, one study demonstrated that a single 100 mg progesterone implant, increasing levels to those of pregnancy, mitigated demyelination and microglia reaction in a focal demyelination mouse model [208].…”
Section: Endocrine-modulated Immune Adaptationsmentioning
confidence: 99%